Destructive Testing of the Weld Joints on Split Sleeve for Branch Connections Repairs - Patek, Marek; Sladek, Augustin; Mician, Milos (Communications - Scientific letters of the University of Zilina, 2015)
New type of repairing technology for branch connection defects on gas pipelines has been designed recently. Repairing technique is based on manufacturing of split sleeve and welding of its parts together and to the repaired pipes by manual metal arc welding technology. Appropriate testing has to be performed to ensure practical and permanent use of such kind of sleeve in commercial area. Destructive testing was performed to confirm quality of the welds on the prototype sleeve repair. Macrostructural and hardness evaluation showed inhomogeneity present in some welds. According to that, microstructure observations, spectral analysis and mechanical tests were performed on the base metal of the sleeve. It has been showed that even when some problems may be present, repairing technique by split sleeve can be still suitable for permanent repairs of the defects of the branch connections.